STUDY OF THE MAIN EXTRUSION PROCESS FACTORS OF GRAIN MIX WITH A PROTEIN FILLING - U. . Chomanov; G. . Zhumalieva; G. . Aktokalova; R. . Kassimbek; A. . Tultabayeva (Алматы технологиялық университетінің хабаршысы, 2021)
Study of the basic extrusion process factors of grain mixture with protein filling. It is noted that the pressure, reaching 4 MPa, was calculated in the extruder during extrusion. The rotation speed of the extruder screwis 55 seconds. Increasing the initial humidity of the mixture also leads to increasingin the rate of extrusion process by reducing the viscosity of the melt in the preforming zone. Found that the temperature distribution of the product along the length of the working zone of the extruder at a constant speed of rotation of the screw is characterized by a sharp increasingin the matrix. In the pre-matriczone, the temperature of the product is constant and when it leaves the matrix quickly decreases to 1000C. Found that at high speed ofthe food mixture is less time in the working area, which reduces the decomposition of nutrients with increasing temperature in the pre-matric zone.This is due to the fact that a high pressures and temperatures in the extruder water exists in the liquid state. At the time of the extrudate exit from the matrix due to the explosive evaporation of water, a large a mount of energy is released and a sharp decrease in temperature occurs.